Determination to Improve the Quality of Human Resources in Public Elementary Schools through Free Nutritious Meal Programs, Talent Management, and Learning Environment - Muhammad Nur; Ahmad Firman; Asniwati (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the determination to improve the quality of human resources in State Elementary Schools through the Free Nutritious Meal Program, talent management, and the quality of the learning environment. The study uses a quantitative approach with the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The research data was obtained through the distribution of questionnaires to teachers of State Elementary Schools in South Jakarta as research respondents. The results of the study show that the Free Nutritious Meal Program, talent management, and the quality of the learning environment have a positive and significant effect on the quality of human resources. These findings show that the improvement of the quality of human resources in basic education is not only influenced by academic factors, but also by the fulfillment of students' nutritional needs, systematic management of student potential, and a conducive learning environment. Therefore, the synergy between nutrition fulfillment policies, talent management development, and improving the quality of the learning environment is an important factor in supporting the development of human resources from school age.